Cyborgs from Fiction to Reality: Marginalized Other or Privileged First? - Stojnić, Aneta (Identities: Journal for Politics, Gender and Culture, 2013)
In this paper I will offer an analysis of cyber technology, cyberspace and cyborg from its appearance in fiction to its contemporary realizations, in order to show symbolic place of cyborg has changed, in the light of contemporary power relations. I will focus on the cyborg figure in literature and film, mainly the cyberpunk genre characteristic for fictionalization of the relations between individual, society and technology. Author(s): Aneta Stojnić Title (English): Cyborgs from Fiction to Reality: Marginalized Other or Privileged First? Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 49-53 Page Count: 5 Citation (English): Aneta Stojnić, „Cyborgs from Fiction to Reality: Marginalized Other or Privileged First?,” Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013): 49-53.